2019
DOI: 10.6008/cbpc2179-6858.2019.004.0010
|View full text |Cite
|
Sign up to set email alerts
|

Estatística multivariada na qualidade da água residuária utilizadas na irrigação na região semiárida brasileira

Abstract: O semiárido do nordeste brasileiro é caracterizado pelas irregularidades pluviométricas e altas temperaturas. Essas características se tornam um fator limitante para a produção agrícola da região, reduzindo a disponibilidade de água, sobretudo que atendam parâmetros ideais para a irrigação. Dessa forma, objetivou-se com este trabalho avaliar a estatística multivariada como ferramenta para analisar a qualidade de água residuária utilizada por agricultores na região semiárida. A coleta dos dados foi realizada em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Regarding the effect of salinity on MI, there was a reduction of 6.26% per unit increase in fertigation ECsol ( Figure 4B). The results obtained in this study are similar to those reported by Dias et al (2005) in melon and similar to those found by Cecílio Filho and Grangeiro (2004) in the triploid watermelon 'Shadow' (46:1 to 51:1).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding the effect of salinity on MI, there was a reduction of 6.26% per unit increase in fertigation ECsol ( Figure 4B). The results obtained in this study are similar to those reported by Dias et al (2005) in melon and similar to those found by Cecílio Filho and Grangeiro (2004) in the triploid watermelon 'Shadow' (46:1 to 51:1).…”
Section: Resultssupporting
confidence: 93%
“…FSI had an average value of 1.01 (Table 1). According to CEAGESP (2003), the fruit is considered cylindrical when the FSI is > 0.7. Therefore, the FSI values, i.e., the LC/TC ratio, of mini watermelon cv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that 30% of the 55 coefficients of correlation can be used to distinguish environments (Table 4); approximately 6% of them are within the 0.6 ≤ r < 0.9 interval, characterized as strong correlation, and 70% are within the 0.3 ≤ r < 0.6 interval, characterized as moderate correlation (CALLEGARI-JACQUES, 2003). 1 pH = potential hydrogen; EC = electrical conductivity; K + = potassium; Na + = sodium; Ca 2+ = calcium; Cl -= chloride; CO 2-3 = carbonate; HCO -3 = bicarbonate; SAR = sodium adsorption ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of results may be laborious when the number of principal components shows a multidimensional space, making the visual inspection of spatial distributions expensive. Cabral et al (2019) evaluated multivariate statistics applied to data related to the use of wastewater for fertigation in the Semiarid region of Brazil (Patos, PB; Santa Luzia, PB; and Santana do Seridó, RN) and found that FA and PCA enabled the selection of two components of water quality indicators for the three municipalities evaluated, which explained 87.8% of the total variance of the data.…”
Section: Resultsmentioning
confidence: 99%